PENERAPAN KEBIJAKAN KOMPETENSI PROFESIONAL GURU DALAM PENGELOLAAN PEMBELAJARAN DI SD NEGERI 225 PALEMBANG - Ida Suryani (Universitas Negeri Medan, 2022)
Abstract: Application of Teacher Professional Competence Policy in Learning Management at SD Negeri 225 Palembang. Professionalism is the most important part in the implementation of learning, this is because the results of the implementation of the learning process to students are strongly influenced by the professionalism of the teacher. A professional is someone who has a job or profession that he does by adhering to high abilities and moral values, and the teacher is one of them. The professional competence of teachers can be seen from their ability to master the learning material in class. Therefore, teachers must have high competence in order to educate great people by mastering the subject matter. Professional teachers have the ability to manage learning from the affective, cognitive, and psychomotor aspects of the students to be educated. This study aims to analyze the application of teacher professional competence in learning management at SD Negeri 225 Palembang. The method used in this study is a descriptive qualitative method, the use of this method is very dependent on the collection of data that can be obtained from observations, interviews, and finally documentation. The application of teacher professional competence at SD Negeri 225 Palembang is carried out well, seen from the implementation of learning which has implemented various standard activities in teaching, besides that an educator must be updated in following the development of the existing curriculum so that teachers do apply pedagogic elements. Keywords: Professional, Teacher, Learning. Abstrak: Penerapan Kebijakan Kompetensi Profesional Guru Dalam Pengelolaan Pembelajaran Di SD Negeri 225 Palembang. Profesional merupakan bagian terpenting dalam pelaksanaan pembelajaran, hal ini dikarenakan hasil dari pelaksanaan proses pembelajaran kepada siswa sangat dipengaruhi dari profesionalitas guru. Profesional merupakan seseorang yang memiliki pekerjaan atau profesi yang dilakukannya dengan berpegang pada kemampuan yang tinggi dan nilai moral, dan guru menjadi salah satunya. Kompetensi profesional guru dapat terlihat dari kemampuannya menguasai materi pembelajaran dikelas. Maka dari itu, guru harus memiliki kompetensi yang tinggi supaya dapat mendidik orang-orang hebat dengan cara penguasaan materi pelajaran. Guru yang profesional mempunyai kemampuan dalam mengelola pembelajaran baik itu dari aspek afektif, kognitif, dan juga psikomotorik dari peserta didik yang akan dididik. Penelitian ini bertujuan untuk menganalisis Penerapan Kompetensi Profesional Guru Dalam Pengelolaan Pembelajaran di SD Negeri 225 Palembang. Metode yang digunakan dalam penelitian ini adalah metode kualitatif yang bersifat deskriptif, penggunaan metode ini sangat tergantung dari pengumpulan data yang dapat diperoleh dari observasi, wawancara, dan terakhir adalah dokumentasi. Penerapan Kompetensi Profesional guru di SD Negeri 225 Palembang dilakukan dengan baik, dilihat dari pelaksanaan pembelajarannya yang telah menerapkan berbagai kegiatan standar dalam pengajaran, selain itu seorang pendidik harus update dalam mengikuti perkembangan kurikulum yang ada sehingga guru memang menerapkan unsur pedagogik. Kata kunci: Profesional, Guru, Pembelajaran.